2018
DOI: 10.1063/1.5021765
|View full text |Cite
|
Sign up to set email alerts
|

Water nucleation in helium, methane, and argon: A molecular dynamics study

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…As discussed in our previous publications 28,30 and in the literature, 76,77,[80][81][82] the type of carrier gas might also have an influence on the nucleation rate. Dumitrescu et al 81 found better thermalization properties for CH 4 compared with Ar. This suggests that a higher CH 4 content would also lead to an increase in J.…”
Section: Third Body Interactionmentioning
confidence: 81%
“…As discussed in our previous publications 28,30 and in the literature, 76,77,[80][81][82] the type of carrier gas might also have an influence on the nucleation rate. Dumitrescu et al 81 found better thermalization properties for CH 4 compared with Ar. This suggests that a higher CH 4 content would also lead to an increase in J.…”
Section: Third Body Interactionmentioning
confidence: 81%
“…As MD uses force fields to describe atomic/molecular interactions, the mostly investigated nucleating species by MD are Lenard-Jones molecules, the simplicity of which help rule out complicating factors and speed up simulation (Angélil et al, 2014;Halonen et al, 2018;Napari et al, 2009;Salvalaglio, Tiwary, Maggioni, Mazzotti, & Parrinello, 2016;Tsai, Smith, & Tiwary, 2019;Zhukhovitskii, 2016). Another substance that has attracted a significant amount of attention is water (Angélil, Diemand, Tanaka, & Tanaka, 2015;Dumitrescu, Huinink, Smeulders, Dam, & Gaastra-Nedea, 2018;Dumitrescu, Smeulders, Dam, & Gaastra-Nedea, 2017;Duška, Němec, Hrubý, Vinš, & Planková, 2015;Matsubara et al, 2007;Tanaka, Kawano, & Tanaka, 2014;Yasuoka & Matsumoto, 1998b;Zipoli et al, 2013). Metal, binary and ternary nucleation systems have also been investigated by MD (Braun, Kalikmanov, & Kraska, 2014;Braun & Kraska, 2012;Lümmen & Kraska, 2006;Römer & Kraska, 2007).…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%